Sea-ice freeboard retrieval using digital photon-counting laser altimetry. Issue 69 (2015) - Farrell, Sinéad L.; Brunt, Kelly M.; Ruth, Julia M.; Kuhn, John M.; Connor, Laurence N.; Walsh, Kaitlin M.
Abstract: Airborne and spaceborne altimeters provide measurements of sea-ice elevation, from which sea-ice freeboard and thickness may be derived. Observations of the Arctic ice pack by satellite altimeters indicate a significant decline in ice thickness, and volume, over the last decade. NASA's Ice, Cloud and land Elevation Satellite-2 (ICESat-2) is a next-generation laser altimeter designed to continue key sea-ice observations through the end of this decade. An airborne simulator for ICESat-2, the Multiple Altimeter Beam Experimental Lidar (MABEL), has been deployed to gather pre-launch data for mission development. We present an analysis of MABEL data gathered over sea ice in the Greenland Sea and assess the capabilities of photon-counting techniques for sea-ice freeboard retrieval. We compare freeboard estimates in the marginal ice zone derived from MABEL photon-counting data with coincident data collected by a conventional airborne laser altimeter. We find that freeboard estimates agree to within 0.03 m in the areas where sea-ice floes were interspersed with wide leads, and to within 0.07 m elsewhere. MABEL data may also be used to infer sea-ice thickness, and when compared with coincident but independent ice thickness estimates, MABEL ice thicknesses agreed to within 0.65 m or better.